Ekspresi mRNA BRLF1 Virus Epstein-Barr dari Biopsi Jaringan Tumor Formalin-Fixed Paraffin Embedeed sebagai Petanda Biologi Molekul Diagnosis Karsinoma Nasofaring - Arin Herkilini; Pancrasia Maria Hendrati; Nur Signa Aini Gumilas; Hidayat Sulistyo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2017)
Nasopharyngeal carcinoma (NPC) is a malignant tumor that grows in the nasopharynx with a predilection in the fossa Rosenmuller. Epithelial malignancies are often found in populations of China and Southeast Asia, including Indonesia. The NPC incidence in year 2008 as many as 84,400 cases and 51,600 of these cases resulted in death. A total of 120 new cases per year NPC found in hospitals Prof. dr. Margono Soekarjo (RSMS), Purwokerto. The NPC is difficult to be diagnose caused its primary tumor lies closed to the skull base as well as various structures of vital organs. Therefore, methods that can detect early NPC required for inspection.The etiology of NPC is multifactorial consisting of genetic factors, factors of infection Epstein-Barr Virus (EBV) and environmental factors.EBV has two phases in the cycle of infection that is the phase of lytic and latent phase.  BRLF1 has an important function as  mediator transition from latent e NPC. The research aimed  to analysis mRNA BRLF1 expression as a biomarker of  NPC diagnosis by RT-PCR and to determine the positivity of RT-PCR method to detect the expression of mRNA BRLF1. The research design was cross sectional study. Samples were FFPE tumor biopsy of NPC WHO III  and the total samples were 22 individu from Department of Pathology Anatomy,  Prof. Dr. Margono SoekarjoHospital, Purwokerto with informed consent. The positivity of mRNA BRLF1 from FFPE tumor biopsy of NPC WHO III  was in 63.6%indicating a high expression.